Enhancing Technology Literacy Competence among Elementary School Teachers in the Era of Educational Digitalization - Wawan Syahiril Anwar; Yudhie Suchyadi (The Indonesian Institute of Science and Technology Research, 2026)
Enhancing national competitiveness in education, particularly at the elementary level, is essential in addressing the challenges of the Educational Revolution 4.0. Teachers, as the key agents of educational transformation, require continuous capacity building in digital and technological literacy to maintain professional excellence and instructional relevance. This community engagement program aimed to strengthen elementary school teachers’ competencies in technology literacy as part of their pedagogical and professional development. The implementation was conducted through a two-phase process focused on integrating technology-based learning media into classroom practices. Data were collected through observations, discussions, and evaluation instruments to assess teachers’ progress. The findings revealed significant improvements in teachers’ ability to utilize digital tools, design innovative instructional media, and apply technology-based learning strategies effectively. Moreover, participants demonstrated increased confidence in sharing educational innovations through scientific publications. The results underscore that developing teachers’ technology literacy not only enhances the quality of learning but also supports sustainable professional growth and contributes to the advancement of digital education ecosystems in elementary schools.